Characterization of plasminogen variants in healthy subjects and plasminogen mutants in patients with inherited plasminogen deficiency by isoelectric focusing gel electrophoresis - Tefs, Katrin; Georgieva, Maria; Seregard, Stefan; Tait, Campbell R.; Luchtman-Jones, Lori; Ziegler, Maike; Hügle, Boris; Schuster, Volker (Thrombosis and Haemostasis, 2004)
Plasmin(ogen) plays an important role in fibrinolysis and wound healing. Severe hypoplasminogenemia has recently been linked to ligneous conjunctivitis. Plasminogen (plg) is known as a polymorphic protein and most of these variants have been identified using isoelectric focusing (IEF) gel electrophoresis. Here, we studied common plg variants from healthy subjects and plg mutants from three patients with hypoplasminogenemia and three subjects with dysplasminogenemia by molecular genetic analysis and IEF. Analysis of 24 healthy subjects showed that subjects with the most common IEF plg phenotype A (n = 12) were homozygous for aspartate at position 453 (453D), while both subjects with IEF plg phenotype B were homozygous for asparagine at this position (453N). Subjects with IEF plg phenotype AB (n = 10) were compound-heterozygous for 453D/453N. Three patients with severe hypoplasminogenemia and different plg gene mutations exhibited characteristic “abnormal” IEF band patterns when compared with IEF plg phenotypes A and B. In all heterozygous family members the observed IEF plg phenotype was derived from the wild type plg molecule only, probably due to low concentration of the mutant plg molecule in plasma. In contrast, in three unrelated subjects with heterozygous dysplasminogenemia an equal “mixture” of wild type and mutant plg was found by IEF analysis. In conclusion, plg phenotyping by IEF in combination with molecular analysis of the plg gene seems to be a useful method for characterization of plg variants and mutants.
Keywords: Isoelectric focusing (IEF) gel electrophoresis; plasminogen (plg); hypoplasminogenemia; dysplasminogenemia; ligneous conjunctivitis